2004
DOI: 10.1038/sj.onc.1207924
|View full text |Cite
|
Sign up to set email alerts
|

Loss of expression of bone morphogenetic protein receptor type II in human prostate cancer cells

Abstract: Bone morphogenetic proteins (BMPs) are members of the transforming growth factor-beta superfamily and signal through a number of membrane receptors. We have previously demonstrated that the loss of expression of BMP receptors (BMPRs) type IA, -IB, and -II (BMP-RIA, -RIB, and -RII) correlates with Gleason score in prostate cancer patients. To evaluate the prognostic value of this observation, we used immunohistochemistry to investigate the expression of BMPRs in association with disease progression in 60 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
116
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(120 citation statements)
references
References 28 publications
3
116
1
Order By: Relevance
“…Bone morphogenetic proteins are expressed in various carcinoma cell lines of gastric, ovarian, prostate, pancreatic and breast origin (Hatakeyama et al, 1993;Kim et al, 2000;Langenfeld et al, 2003). Studies using a variety of tumor systems revealed that BMP signaling produces a complex set of effects in cancer, in which they can be either protumorigenic or antitumorigenic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone morphogenetic proteins are expressed in various carcinoma cell lines of gastric, ovarian, prostate, pancreatic and breast origin (Hatakeyama et al, 1993;Kim et al, 2000;Langenfeld et al, 2003). Studies using a variety of tumor systems revealed that BMP signaling produces a complex set of effects in cancer, in which they can be either protumorigenic or antitumorigenic.…”
Section: Discussionmentioning
confidence: 99%
“…BMPs are expressed in a variety of human carcinoma cell lines (Hatakeyama et al, 1993;Kim et al, 2000;Langenfeld et al, 2003), and mutations of the human ACVR2 gene, encoding ALK2, have been reported to be responsible for the development of juvenile polyposis in some patients (Howe et al, 2001;Haramis et al, 2004). BMP signaling has also been shown to inhibit tumorigenesis of several tumor types, including brain tumors, basal cell carcinomas of the skin and gastric cancer (Piccirillo et al, 2006;Sneddon et al, 2006;Bleuming et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hardwick et al [16] investigated the immunoexpression of BMP-2 in intestinal colon specimens of patients with familial adenomatous polyposis and observed the loss of BMP-2 expression in dysplastic areas of the microadenoma, when compared to the superficial layer of normal epithelium adjacent to the tumor that exhibited significant immunoreactivity. Kim et al [17,18] observed elevated expression of BMP receptors in normal prostatic and bladder tissue. These studies suggest that the responsiveness to BMPs and their receptors may vary among different cell types, including those of the same embryonic origin.…”
Section: Discussionmentioning
confidence: 99%
“…In metastatic OSCC specimens, expression tended to be weak in all cases analyzed. During carcinogenesis, especially in the more advanced stages of the disease, neoplastic cells commonly lose their responsiveness to BMPs, either due to the loss of expression of their receptors or to the increased synthesis of BMP inhibitors such as noggin [4,17,18,24]. The loss of expression of BMP receptors, especially BMPR-IA, is expected in many human cancers such as prostate, bladder, breast, and intestinal colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional signalling pathways are acknowledged to play important roles in malignant disease, with the bone morphogenetic protein (BMP) signalling pathway emerging as important in multiple cancers (Nagatake et al, 1996;Tamada et al, 2001;Baldus et al, 2004;Dai et al, 2004;Kim et al, 2004). It is well recognised that the BMP signalling pathways are crucial for all stages of embryonic development, including regulation of lung development and airway branching (Weaver et al, 1999;Lu et al, 2001;Rosendahl et al, 2002).…”
mentioning
confidence: 99%